Pengaruh Tenaga Kerja Asing Terhadap Kesempatan Kerja Bagi Tenaga Kerja Lokal di Indonesia - Abrarurrazi, Teuku; Mahrizal, Mahrizal (Universitas Teuku Umar, 2024)
Indonesia has a lot of human resources, but not all human resources are competent. People who are of working age are referred to as workers. Labor is every person who has the ability to do work that produces goods and services that are beneficial to society as a whole and to themselves. According to this understanding, the results of labor are not only enjoyed by workers, but also enjoyed by society as a whole. This shows how important labor is in people's lives and that many people enjoy its results. The absence of a competent workforce is one of the reasons why there is so much unemployment. One of the factors causing the increase in unemployment in Indonesia is a culture of laziness. This research aims to determine how foreign workers influence employment opportunities for local workers in Indonesia. This study uses a simple linear regression statistical model to test its hypothesis. The variables employment opportunities (y) and foreign workers (x) are used. Secondary data from time series was used in this study. H0 is accepted and Ha is rejected. Therefore, it can be concluded that the variable foreign workers has an insignificant and negative effect on job opportunities for local workers in Indonesia. The suggestions that can be given are: For the government, researchers suggest opening more job opportunities for the community, especially local communities, and reducing providing employment opportunities to workers outside the region